2022
DOI: 10.1002/acr.24752
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Cannabis Use Among Adults With Rheumatic Diseases: Results From a 2014–2019 United States Observational Study

Abstract: Objective. Despite advances in treatments and outcomes among patients with rheumatic diseases, there is an unmet need in pain management. Cannabis has emerged as a potential opioid-sparing alternative, with arthritic pain as a commonly cited reason for medicinal cannabis use. However, little is known, and we set out to understand patterns of cannabis use in a US-wide rheumatic disease population.Methods. The study included participants in FORWARD, The National Databank for Rheumatic Diseases. Participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…In patients with rheumatic diseases, we found few cannabis users (4.6%), but a significant number of patients were in favour of using therapeutic cannabis in the future while being supervised or when cannabis is legalised in France. These results are in line with those of Wipfer which showed an increase in cannabis consumption in adults with rheumatic diseases in the USA in 2019 (5).…”
Section: Sirssupporting
confidence: 91%
“…In patients with rheumatic diseases, we found few cannabis users (4.6%), but a significant number of patients were in favour of using therapeutic cannabis in the future while being supervised or when cannabis is legalised in France. These results are in line with those of Wipfer which showed an increase in cannabis consumption in adults with rheumatic diseases in the USA in 2019 (5).…”
Section: Sirssupporting
confidence: 91%
“…Although broad expertise was recruited and an extensive list of interventions was considered in this guideline, we could not ensure expertise in every area of integrative RA management or consider all possible integrative interventions. For example, members of the Patient Panel inquired about use of cannabinoids as an RA treatment, given the rising prevalence of their use in rheumatic diseases (29,30). Cannabinoids were not included in this guideline, and emerging evidence for cannabidiol, a pharmacologic therapy that is not FDA-approved for RA, is being synthesized in a living systematic review through a joint US Department of Veterans Affairs and Center for Evidence-Based Policy at Oregon Health & programs, exercise programs, and weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…4,37,42,47 Use of many analgesic medications is contraindicated by kidney or liver disease and prescription psychotropic medications or anticoagulants, 14,59 which may limit pain management options for older VHA patients and thus lead to cannabis use. Cannabis use for managing symptoms of pain and arthritis is increasing among adults age $65 61 and may be associated with a higher risk of CUD. 19 Although many adults use cannabis without developing CUD or other harms, 34 we demonstrated that veterans with chronic pain have experienced disproportionately greater increases in the prevalence of CUD diagnoses than veterans without chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…4,37,42,47 Use of many analgesic medications is contraindicated by kidney or liver disease and prescription psychotropic medications or anticoagulants, 14,59 which may limit pain management options for older VHA patients and thus lead to cannabis use. Cannabis use for managing symptoms of pain and arthritis is increasing among adults age ≥65 61 and may be associated with a higher risk of CUD. 19…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation